Gayby Baby – From the politics of representation to the politics of care. (October 2018) - Skattebol, Jennifer; Newell, Maya
Background: Real life stories can enable audiences to empathise with the experiences of marginalised groups and communities and are extremely powerful tools in struggles for equality. High-quality documentary research can convey the life experiences of marginalised peoples in ways that are recognisable to them and which further their struggle for equality. Often, marginalised people are represented by 'filmmakers' eager to capitalise on the affect produced by detailed renditions of everyday political struggles. However, film-makers are rarely trained in how to empower participants to understand film-making and distribution processes. These understandings and dialogic processes are important if participants are to have a real say in how they are represented. Process: In 2011, Maya Newell and Charlotte Mars began to develop an observational feature documentary Gayby Baby (2015) focused on same-sex families, for the first time revealing the child's perspective on debates concerning Lesbian, Gay, Bisexual, Trans, Intersex, Queer and their children's equality. They were interested in empowering participants to have a real say in the film. Jen Skattebol's family was one of the four families featured in the film. This shared activist experience grounds the authors' discussion of ethical care in representative practices. Discussion: Recently, documentary film-making and academic research has seen the emergence of a new value system that measures success in terms of 'impact' in the public sphere. This developing interest amplifies the ethical issues involved in representational work and raises new questions concerning the implications of subject participation in the development of resources that aim to improve health and well-being in broad political terms. This article sketches out the contours of a more ethical form of social impact making that grew out of kitchen table conversations between documentary subject and maker – the researched and researcher. Ethical frameworks of care need to be recalibrated in line with the issues foregrounded by burgeoning social impact agendas.